Cooperation in the Short and in the Long Run. - Young, H; Foster, D (Elsevier, 1991)
The long-run behavior of economic and biological processes is often dramatically altered when stochastic influences are taken into account. In fact, the smaller the noise, the more drastic the change can be. This seemingly paradoxical point is illustrated with the evolution of cooperation in repeated Prisoner's Dilemma.